Perlakuan Pajak Pertambahan Nilai (PPN) Atas Debit Note Ekspor Jasa Kena Pajak - Dian Wahyudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2015)
This study was conducted to determine about the debit notes is a taxable and tariffs 10% ( ten percent ) on export of taxable service if it is reviewed by taxable supplies, and to determine the treatment of VAT on Debit Note reviewed by the concept of destination principle and to determine whether it is acceptable in tax regulation of Indonesia if It’s issued a Debit Note for collecting of company income and to estimate how much penalties arise. This study used qualitative methods with qualitative descriptive analysis. The object of research is based on data available at the company that is secondary data. Data collection techniques are Library research.The results of data processing that the Debit Note is an taxable of VAT. In terms of destination Principle Debit Note is taxable to VAT 0 % (Zero Percent) for the shipping charge, the Minimum Order Quantity (MOQ) charge and cancel orders charge / penalty fees. Debit Note Billing mechanism is allowed in tax regulation as long as there is a document whose position equivalent to tax invoice for canceled order charge/penalty fees, but charge for shipping and the Minimum Order Quantity (MOQ) charge don’t allow in the tax regulation because it is non-compliance of the material terms of the tax invoice. As a result of the Debit Note that issued raised the sanctions of Article 14 paragraph (2) of general provisions and taxation procedures for 2 % of the tax base.Based on the suggested better in making commercial document to charge must analyze aspects of taxation in order to prevent tax penalties in this case to issue Debit Note need to create a document that is equivalent to a Tax Invoice because mechanism of the Debit Note is taxable of VAT.